Estimating the deferred value of pathogen genomic data for secondary use - Vitali Sintchenko; Eby M. Sim; Carl J. E. Suster (Scientific Data)
Abstract The COVID-19 pandemic has illuminated the utility of pathogen genomics and highlighted roadblocks to international data sharing. This article describes the deferred value of pathogen genomics data for secondary use using a set of 10,110 assembled genomes of Vibrio cholerae shared via international repositories between 2010 and 2024 as an illustrative representation of a pandemic disease. Trends in the quality, representativeness, and timeliness of data sharing as well as the increasing role of microbiology services as genomic data providers resulting from gradually improving access to sequencing technologies in countries with a high burden of disease were identified. The deferred value of individual and aggregated genomic data was tracked over time and mapped to geographical hot spots of cholera. The time lag between the collection of the samples for V. cholerae cultures and the submission of the genome to an international database remained eight years on average. The data value assessment described here paves the way for the international mobilization of quality microbial genomic data for global health and knowledge discovery.